The Effect of Fixed Asset Administration and Organizational Commitment on The Quality Of SKPD Financial Statements In The Regional Government of West Bandung Regency - Fitra Nur Rahima; Berliana Karlinda; Silviana (International Journal of Social Science and Business, 2024)
Financial statement contained important information that allowed for accurate policy implementation. Financial statement must benefit all stakeholders. However, BPK's review found that the financial statement still contained irrelevant information. This was related to unverified National Health Insurance member data. Therefore, realizing the value of spending must be supported by reliable data, leading to overspending. Accordingly, the purpose of this study was to examine the effect of fixed asset administration and organizational commitment on the quality of Regional Facilities Working Unit (SKPD) financial statement in the Regional Government of West Bandung Regency. The verification method was used in the study to assess the validity of the hypothesis made through the collection of field data. The purpose of this study was to determine the effect of fixed asset administration (X1) and organizational commitment (X2) on the quality of SKPD Financial Statements in The Regional Government of West Bandung Regency (Y). The survey included 94 respondents of 47 SKPD from the Regional Equipment Working Unit (SKPD). SPSS version 16 software was used to perform data analysis, including validity, reliability, and linear regression. The results showed that the regression analysis demonstrated the effect of fixed asset administration and organizational commitment on the quality of SKPD Financial Statements in The Regional Government of West Bandung Regency. Overall, good fixed asset administration and high organizational commitment were important aspects to improve the quality of SKPD financial statements in the Regional Governments of West Bandung Regency.